(untitled) (Medico Legal Update, 2020)
Objectives: The purpose of this study was to examine the effects of acute exercise intensities on changes in blood lipids and growth factors in middle school students with intellectual disabilities. Method: The study participants were randomly assigned into low intensity (n = 8), moderate intensity (n = 9) and high intensity (n = 9) groups. Acute exercise intensities was classified into low intensity (40 54% HRR), moderate intensity (55 69% HRR) and high intensity (70 85% HRR) using heart rate reserve (HRR). Blood lipids (total cholesterol, Triglyceride, high-density lipoprotein cholesterol, Low-density lipoprotein cholesterol) and growth factors (insulin-like growth factor-1, growth hormone, thyroxine, thyroid stimulating hormone) were measured before and after executing the physical activity program. Findings: According to the results for blood lipids, high-density lipoprotein cholesterol (HDL) was significantly increased in the high-intensity group compared to the low-intensity group. For growth related hormones, insulin-like growth factor-1 (IGF-1) was significantly increased after exercise in the high-intensity group compared to the moderate-intensity group. Applications: When the same amount of acute exercise was given to middle school students with intellectual disabilities, HDL was found to increase by the largest amount in the high-intensity group. IGF-1 was also found to be most effective in the high-intensity group. Future studies need to comprehensively account for sex and level of obesity.